2022
DOI: 10.1097/jcn.0000000000000913
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Illness Perception and Adherence to Treatment in Slovak Patients With Hypertension

Abstract: BackgroundLack of adherence to treatment in patients with arterial hypertension leads to poor blood pressure control, increased morbidity and mortality, and increased costs to health and social care. Regular assessment of treatment adherence as well as factors influencing it is important to improve patient adherence and consequently increase treatment efficacy. Personal beliefs, particularly illness representations, are significant factors that influence adherence.ObjectiveThe aim of this study was to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It can affect the patient's psychological state and determine his or her level of self-regulation [48]. Positive disease awareness is conducive to enhancing their awareness of preventive health care and promoting medical compliance behaviors, thereby improving patients' health and long-term quality of life [49][50][51][52]. However, the stronger the individual's negative disease perception, the more severe the symptoms they experience, which may aggravate the patient's negative emotions, reduce the confidence in coping with stressful events [19], reduce the individual's willingness to contact the surrounding things and the environment, and increase social alienation feel.…”
Section: Ip Is Positively Correlated With Social Alienationmentioning
confidence: 99%
“…It can affect the patient's psychological state and determine his or her level of self-regulation [48]. Positive disease awareness is conducive to enhancing their awareness of preventive health care and promoting medical compliance behaviors, thereby improving patients' health and long-term quality of life [49][50][51][52]. However, the stronger the individual's negative disease perception, the more severe the symptoms they experience, which may aggravate the patient's negative emotions, reduce the confidence in coping with stressful events [19], reduce the individual's willingness to contact the surrounding things and the environment, and increase social alienation feel.…”
Section: Ip Is Positively Correlated With Social Alienationmentioning
confidence: 99%
“…Additionally, age emerges as a significant factor, with younger patients exhibiting higher adherence rates. 7 , 10 Beyond individual factors, healthcare-team-related issues, such as communication gaps and prolonged waiting times during appointments, have been linked to poorer medication adherence. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Simplifying drug regimens has proven effective, 11 with studies revealing that patients using one or two antihypertensive pills demonstrate greater adherence compared to those with more complex regimens. 5 , 6 , 10 In Egypt, a study identified a positive correlation between simplified dosing schedules and improved adherence. 7 …”
Section: Introductionmentioning
confidence: 99%